2016
DOI: 10.1016/j.fuproc.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Syn-gas ratio via bireforming over coke-resistant Ni/Mo2C catalyst

Abstract: This study demonstrates the ability of Ni/Mo 2 C to catalyze the Methane Bireforming Reaction (combined Dry Methane Reforming Reaction, CH 4 + CO 2  2H 2 + 2CO, and Steam Methane Reforming Reaction, CH 4 + H 2 O  3H 2 + CO). By varying the ratio of CO 2 :H 2 O, the resulting H 2 :CO ratio could be tuned from 0.91 to 3.0, covering a wide range of Syn Gas (H 2 + CO) ratios relevant to various hydrocarbon syntheses. We also document the unusual deactivation behavior of Ni/Mo 2 C in this system. The catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…In recent years, interstitial compounds of metal carbide, nitride, and phosphides have received attention for catalyst development . Among these interstitial compounds for DRM, predominant attention has been drawn to Mo-based carbide, nitride, and phosphide catalysts. Especially, extensive studies on Mo 2 C have shown that this compound has similar activities compared with noble metals (Pd, Pt) at slightly elevated pressures (2 bar) in DRM. However, for single-metal carbides, high reaction pressures are required to achieve good activity, as the catalyst deactivates at low pressures because of oxidation by CO 2 to form ineffective oxides. Recently, Fu et al showed that bimetallic Ni- and Co-doped molybdenum nitride exhibited high catalytic activity and are resistant to oxidation at atmospheric pressure . Similarly, a study of DRM with molybdenum phosphide (MoP) catalyst showcased high coking and oxidation resistance with better stability compared with Ni/Mo 2 C catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interstitial compounds of metal carbide, nitride, and phosphides have received attention for catalyst development . Among these interstitial compounds for DRM, predominant attention has been drawn to Mo-based carbide, nitride, and phosphide catalysts. Especially, extensive studies on Mo 2 C have shown that this compound has similar activities compared with noble metals (Pd, Pt) at slightly elevated pressures (2 bar) in DRM. However, for single-metal carbides, high reaction pressures are required to achieve good activity, as the catalyst deactivates at low pressures because of oxidation by CO 2 to form ineffective oxides. Recently, Fu et al showed that bimetallic Ni- and Co-doped molybdenum nitride exhibited high catalytic activity and are resistant to oxidation at atmospheric pressure . Similarly, a study of DRM with molybdenum phosphide (MoP) catalyst showcased high coking and oxidation resistance with better stability compared with Ni/Mo 2 C catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Brush and co-workers explored the performance of Ni/Mo2C for bi-reforming reaction with CH4 and CO2 conversion of 70.5% and 99.8% respectively. They also observed no signs of coking despite conducting the reaction with excessive methane at high temperature [57].…”
Section: Catalyst Supportmentioning
confidence: 99%
“…Furthermore, the variation of CO 2 /H 2 O ratio can tune the produced H 2 /CO ratio from 0.91 to 3.0, covering a wide range of syngas composition for various downstream hydrocarbon synthesis. So far, efforts for the bireforming have been mainly focused on Ni‐based catalysts …”
Section: Dry Reforming Of Methanementioning
confidence: 99%